Improvement of anchovy surimi gel (Engraulis ringens) by adding giant squid arm surimi (Dosidicus gigas) - Maza-Ramírez, Santos (2020)
The aim of this study was to improve the functional properties of anchovy surimi by adding giant squid arm surimi. Texture and colour characteristics of six proportions of giant squid arm surimi / anchovy surimi (0/100, 20/80, 40/60, 50/50, 70/30, 100/0) were evaluated. The results showed that the texture characteristics of the gel and colour improved considerably for the mixture of surimi with 70/30, obtaining 522.2 g of hardness, 8.2 mm of elasticity, 429.5 g * cm of gel strength, and the values of L* and a* were 74.30 and -0.85, respectively. This result indicates that the 70/30 mixture of surimi with 70/30 is the best proportion to improve the texture and colour properties of the anchovy surimi gel. The optimal ratio was corroborated by linear programming, where an improvement in the price of anchovy surimi was obtained by the addition of giant squid surimi.